2018
DOI: 10.12783/dtssehs/icaem2017/19137
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Emotional Labor and Mental Health of College Teachers: the Mediate Effect of Emotional Exhaustion

Abstract: Abstract. This study explores the relationship between emotional labor and mental health and the mediate effect of emotional exhaustion. Emotional Labor Scale, Mental Health Scale and Emotional Exhaustion Scale for teachers are used to investigate a survey of 710 college teachers in Shandong province. The results show that college teacher is a profession required high level of emotional labor, the most frequently used strategy is automatic acting and then the deep acting. Surface acting positively correlates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
1
4
0
2
Order By: Relevance
“…Compared to surface acting, deep acting, and job burnout results, this study found that when medical workers adopted more surface acting, they were more likely to suffer from job burnout, which is consistent with previous results (Hu & Sun, 2016;Li et al, 2015;Zhang, 2015aZhang, , 2015bZhang, Loerbroks, et al, 2018;. These findings have some implications for resolving doctor-patient conflicts and reducing the job burnout of healthcare workers, for example, strengthening social health service centres and family-contracted doctors, which are currently being promoted.…”
Section: Correlation Between Emotional Labour Strategies and Job Burnoutsupporting
confidence: 91%
See 1 more Smart Citation
“…Compared to surface acting, deep acting, and job burnout results, this study found that when medical workers adopted more surface acting, they were more likely to suffer from job burnout, which is consistent with previous results (Hu & Sun, 2016;Li et al, 2015;Zhang, 2015aZhang, , 2015bZhang, Loerbroks, et al, 2018;. These findings have some implications for resolving doctor-patient conflicts and reducing the job burnout of healthcare workers, for example, strengthening social health service centres and family-contracted doctors, which are currently being promoted.…”
Section: Correlation Between Emotional Labour Strategies and Job Burnoutsupporting
confidence: 91%
“…In empirical studies on the relationship between emotional labour strategies and job burnout, there are obvious differences in the findings for different occupational groups. Most studies on medical workers show that their surface acting is significantly positively correlated with job burnout, whereas their deep acting is significantly negatively correlated with job burnout (Hu & Sun, 2016; Li et al., 2015; Long et al., 2013; Zhang, 2015b; Zhang, Wang, et al., 2018). However, some scholars have pointed out that surface acting inhibits the generation of a reduced personal sense of achievement in medical workers (Luo et al., 2008; Wang, 2015; Xiong, 2014; Zhou, 2018).…”
Section: Emotional Labour Strategies and Job Burnoutmentioning
confidence: 99%
“…Research also shows university lecturers performed higher emotional labour (Berry & Cassidy, 2018). Additionally, educator who engaged in higher education such as college are more likely engaged in automatic acting which is the emotional labour strategies-genuine acting (Hu, Wang, & Yang, 2017).…”
Section: Emotional Labour and Employee's Well-beingmentioning
confidence: 86%
“…It modifies their thinking to the cognitive assessment system, creating a balance between internal and external emotions and a resource acquisition strategy that lowers emotional disease (Zapt, 2002). Last but not least, sincere labour improves psychological well-being (Cheung & Lun, 2015;Hu et al, 2017;Zapt, 2002). Additionally, a large body of research (Ashforth & Hymphrey, 1993;Brotheridge & Grandey, 2002;Dall'Ora et al, 2016;Hochschild, 1983;Kinman & Leggetter, 2016, p. 2013Vermaak et al, 2017) demonstrated the effect of emotional labour on psychological well-being.…”
Section: Discussionmentioning
confidence: 99%
“…In response to stressful circumstances, surface and deep acting are more common than the study implies, and expressing genuine emotions is more often than the analysis suggests. It relates to how players must control their emotions when interacting with a demanding consumer and express them through deep acting (Hu et al, 2017). Additionally, when people express their true feelings, improved service quality results from sincerity (Diefender et al, 2005;Sohn & Lee, 2012).…”
Section: Introductionmentioning
confidence: 99%